Associations between Electroencephalographic Variables, Early Post-Traumatic Seizure Risk, and Outcomes following Pediatric Severe Traumatic Brain Injury - Nickerson, Taylor E.; Villo, Lauren; Eisner, Mariah; Lovett, Marlina E.; Chung, Melissa G.; O'Brien, Nicole F.; Sribnick, Eric A.; Ostendorf, Adam P. (Journal of Pediatric Intensive Care, 2022)
Early post-traumatic seizures (PTS) are associated with worse outcomes in children with traumatic brain injury (TBI). Our aim was to identify the association between continuous electroencephalogram (cEEG) characteristics and early PTS risk following pediatric severe TBI. We also evaluated the relationship between cEEG background features and outcomes. A single-center retrospective cohort study was performed on children between 0 and 18 years of age admitted to the pediatric intensive care unit from 2016 to 2019 with severe TBI and cEEG monitoring within 7 days of injury. Raw cEEG tracings were reviewed by an epileptologist in accordance with American Clinical Neurophysiology Society (ACNS) Critical Care EEG terminology. Univariate comparisons were made between children with and without early PTS, as well as between those with and without varying cEEG background features. Eighteen children (31%) of the 59 included had early PTS. Interictal abnormalities, inclusive of sporadic spikes and sharp waves, rhythmic delta activity, or lateralized periodic discharges (LPDs) were more common among children with seizures (100 vs. 22%; p < 0.01). LPDs were also more common in the seizure group (44 vs. 2%; p < 0.01). Background discontinuity was associated with worse Glasgow Outcome Scale—Extended Pediatric Version (GOS-E Peds) scores at discharge and 3-, 6-, and 12-month post-discharge (p < 0.01). Lack of reactivity was also associated with worse GOS-E Peds scores at 3-, 6-, and 12-month post-discharge (p < 0.01). Interictal abnormalities and LPDs were each associated with early PTS following pediatric severe TBI. Larger studies should evaluate if high-risk patients would benefit from prolonged cEEG monitoring and/or more aggressive anti-seizure prophylaxis. Discontinuity and lack of variability were associated with worse outcomes. Future studies should attempt to clarify their role as potential early markers of prognosis.
Keywords: electroencephalography; severe TBI; pediatrics; post-traumatic seizures; outcome